PENGEMBANGAN SISTEM MANAJEMEN STOK BARANG BERBASIS WEB PADA ARFI STIK KEJU DAN BROWNIES BATIK TANGSEL - M Farid Zulianto; Rafi Basthara; Reza Shahrul Romadoni; Ari Syaripudin (CV. Denasya Smart Publisher, 2025)
The implementation of the Internship Program (Kuliah Kerja Praktek / KKP) aims to equip students with practical experience in the professional world while allowing them to apply the theoretical knowledge gained during their studies. This activity was carried out at Arfi Stik Keju and Brownies Batik Tangsel, a micro, small, and medium enterprise (MSME) that produces snack foods. One of the main challenges faced by this MSME is the inventory management process, which is still done manually, making it susceptible to errors, difficult to monitor in real time, and causing delays in generating reports. To solve these problems, a web-based stock management system was developed using PHP and MySQL technologies. This system enables real-time stock monitoring, improves the accuracy of inventory records, and accelerates report preparation. The research methods used include literature study, interviews, and direct observation. The result of this internship is a prototype of a web-based stock management system that can be accessed through various internet-connected devices, supporting the management in making data-driven decisions. It is expected that this system will help improve operational efficiency and contribute to the business development of Arfi Stik Keju and Brownies Batik Tangsel.